The evidence for urology - Dawson, Chris; Muir, Gordon (Tfm Pub., 2005)
Approximately 45 chapters written by leading international authorities. Each chapter analyses the available literature to produce an authoritative statement about the management of urological disorders. The book includes a concise summary of the best available scientific evidence providing up-to-date information.